2016
DOI: 10.1111/acps.12630
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and mortality risk in a dementia cohort: data from SveDem, the Swedish Dementia Registry

Abstract: Antidepressant treatment is common among patients with dementia. Use of antidepressants during prodromal stages may reduce mortality in dementia and specifically in Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 51 publications
(55 reference statements)
1
14
1
Order By: Relevance
“…Antidepressant treatment was associated with a reduced mortality risk of 18 À 19%, in accordance with one previous study with the same reduced mortality risk (Enache et al, 2016). We also found that AChEI treatment was associated with a 19 À 20% decrease in mortality.…”
Section: Medication and Mortalitysupporting
confidence: 92%
“…Antidepressant treatment was associated with a reduced mortality risk of 18 À 19%, in accordance with one previous study with the same reduced mortality risk (Enache et al, 2016). We also found that AChEI treatment was associated with a 19 À 20% decrease in mortality.…”
Section: Medication and Mortalitysupporting
confidence: 92%
“…This likely holds for our study as well, given the fact that 15% of people in our sample were diagnosed with two or more different dementia disorders during the observed period (data not presented in tables). The high misclassification of dementia disorders in the present study may underestimate clinical differences between different types of dementia that were found more pronounced in previous studies [ 26, 38, 46 ].…”
Section: Discussioncontrasting
confidence: 58%
“…Anti-depressant medications find frequent use in older people, with average prevalence rates of approximately 25% [15,16]. Recent evidence suggests no association between antidepressant prescriptions and augmented risk of all-cause mortality [17,18].…”
Section: Studies Of Other Psychotropic Medications and Mortality In Omentioning
confidence: 99%